Transferrin C subtyping in Malaysians and in Indonesians from North Sumatra - Tan, S.G.; Gan, Y.Y.; Asuan, K. (Springer-Verlag, 1982)
Malays, Chinese, and Indians from Peninsular Malaysia; Ibans and Bidayuh from Sarawak State; Kadazans from Sabah State, Northern Borneo; and Bataks, Minangkabau, and Javanese from North Sumatra, Indonesia, were subtyped for transferrin C by polyacrylamide gel isoelectric focusing. All nine populations studied are polymorphic for two alleles, TfC1 and TfC2. TfC3 was polymorphic in six populations and present as a rare variant in the other three. The frequency of TfC1 ranged from 0.855 in Bidayuh to 0.711 in Javanese, that of TfC2 from 0.231 in Indians to 0.113 in Bidayuh, and that of TfC3 from 0.030 in Javanese and Chinese to 0.008 in Bidayuh. TfDchi is polymorphic in all the populations that we studied except in Minangkabau, in whom it is present as a rare variant, and in Indians, in whom it is absent.